Princípios constitucionais de direito eleitoral - Vargas, Alexis Galiás de Souza (2009)
This study aims the identification and theoretical development of the constitutional principles of electoral law. The Constitution is full of principles, which are legal rules with differentiated normativity, whose application demands a specific methodology. Thus the Theory of Principles took a central role in the new constitutional hermeneutic. The identification and construction of principles, and the methodology used to extract its normativity, are tasks of utmost importance for the interpretation and application of the Constitution. Nevertheless, regardless of how much the national studies on constitutional principles evolved, we see that they have not focused on the field of application of the Constitution that falls specifically on the electoral legal order. Consequently, the electoral law resents the lack of systematization of its rules and a theoretic referential to support it and guide its interpretation and integration. This study humbly seeks to collaborate in the overcoming of these difficulties. It seeks to identify and help the construction of what would be the constitutional principles of electoral law. In order to reach this daring objective, we start from a clear stance regarding the Theory of Principles and the definition of a scientific methodology, within a dogmatic perspective, which allows the outlining of a safe path in the disclosure and construction of these principles, to then pursue the field of constitutional electoral order. It is not a study that seeks to exhaust the subject. This work is necessarily incomplete, considering that principles, by their own nature, can be implicit and constructed through an evolutionary interpretation. On the other hand, the study allows one to safety attest that the rules expressed herein are constitutional principles that shall inform the Brazilian electoral law. The result of this study is a list of constitutional principles of electoral law, classified according to their scope and with the definition of their contents, theoretic justifications and their jurisprudential development